Colour Memory Analysis for Selected Associative Colours - Marta Stjepić; Sabina Bračko (Tekstilec, 2021)
Colours are one of the most important factors in everyday life. The exact number of existing colours is not yet fully known. Nevertheless, people are known for having poor colour memory. The ability to remember colours depends both on the characteristics of an individual and the situation in which the colour needs to be recalled. The field of colour memory (perception and memory of unusual colours) has been very poorly researched. The aim of this study was to analyse long-term colour memory for selected associative colours, comparing it with short-term colour memory. The research approach was based on observation, with observers observing for a period of time a particular colour, image, or a descriptively given reference colour. Colour was treated separately from associations in the first part, and related to associations in the second and third parts. The first part contained all the reference colours shown independently of associations, the second part contained grayscale images of brands, and the third part comprised descriptively given colours. The result analysis showed that people remember colours very poorly. Observers generally performed better in testing short-term memory. Moreover, the way the template was presented had a noticeable effect on the long-term colour memory. When the image was given in grey, the results were better. The descriptive rendering of reference colours shown did not contribute to better results. The gender of observers did not significantly affect the results.